The eruption of the Peteroa volcano (35°15'S, 70°18'O) on 4th September, 2010 - Haller, M.J. (2011)
The Peteroa volcano, located in the SouthernVolcanic Zone of the Andes at 35°15'S latitude, erupted for about 48 days, beginning on September 4th, 2010. After a period of increased fumarole activity, the eruption began with a strong eruption column of ca. 1,800 m in height, to continue later with a weak column of 200 meters. Particulate emitted material contains mainly glass shards and glass fragments with subordinate crystaloclasts. The tephra fallout was mainly accumulated in the vicinity of the volcano, while in more remote areas formed only a thin layer. Due to the low volume of ejected tephra and limited volcanic ash spread, and the fact that the vicinity o the volcano was uninhabited, the eruption of 2010 did not have much effect on people.